If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2t - 1=(t+7)
We simplify the equation to the form, which is simple to understand
2t-1=(t+7)
Remove unnecessary parentheses
2t-1=t+7
We move all terms containing t to the left and all other terms to the right.
+2t-1t=+7+1
We simplify left and right side of the equation.
+1t=+8
We divide both sides of the equation by 1 to get t.
t=8
| 9x^2+24x=16 | | 16+b^2=64 | | 5x(x-1)+5=7+x(1-2x) | | 100+8x=12x | | -39x-26x=-39 | | 36x^4-25=0 | | (x-2)+y^2=64 | | A=5-2(n-1) | | 46=654 | | 5/9=2x=13/9 | | 10x^5=100 | | 8x+y=-6 | | y=tan*(5*X) | | -32(16x)-y+9=0 | | 2.4m-1.2=0.6m | | f(x)=4x^4-5x-3 | | 8x+12y=9 | | 3/8x9= | | (2u+5x-6)(u+7x)= | | 8x-(5-1x)=-44 | | (2u+5x-6)x(u+7x)= | | -32x-y+9=0 | | 2x^3+x^2+5x-3=0 | | -8/7=-1/3w-5/6 | | 4(b+4)-2=-5(B+7)+2b | | 6+6x=-6x-66 | | 36x^2-6=12x^2-3 | | f(x)=8x^2 | | -1/2-4/3v=1/5 | | 1+5x-8=-39 | | -2.74+m=-9.2 | | 199=44-v |